2007
DOI: 10.1016/j.otohns.2007.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Outcomes of Balloon Catheter Sinusotomy: A Multicenter 24‐Week Analysis in 115 Patients

Abstract: Balloon catheter technology appears safe and effective in relieving ostial obstruction. Patients were pleased and indicated that they experienced symptomatic improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
193
0
8

Year Published

2010
2010
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(215 citation statements)
references
References 17 publications
(28 reference statements)
14
193
0
8
Order By: Relevance
“…The goal of EES is to increase ventilation and drainage of the paranasal sinuses (PNS) involved, enabling the proper functioning of mucociliary movements in the nasal and PNS mucosa, thus facilitating the drainage of these cavities and enabling the penetration of medication and solutions for nasal flushing [1][2][3][4] . This method, despite bearing numerous benefits when compared to the conventional open procedures, still has some inherent challenges and limitations, especially because it ends up removing bone tissue and nasal mucosa fragments, which can cause bleeding, temporary physiological changes to the nasosinusal mucosa, especially the paradox reduction of mucociliary movements in the post-operative period and local scar fibrosis, which can cause re-obstruction of the treated PNS 1,2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The goal of EES is to increase ventilation and drainage of the paranasal sinuses (PNS) involved, enabling the proper functioning of mucociliary movements in the nasal and PNS mucosa, thus facilitating the drainage of these cavities and enabling the penetration of medication and solutions for nasal flushing [1][2][3][4] . This method, despite bearing numerous benefits when compared to the conventional open procedures, still has some inherent challenges and limitations, especially because it ends up removing bone tissue and nasal mucosa fragments, which can cause bleeding, temporary physiological changes to the nasosinusal mucosa, especially the paradox reduction of mucociliary movements in the post-operative period and local scar fibrosis, which can cause re-obstruction of the treated PNS 1,2 .…”
Section: Introductionmentioning
confidence: 99%
“…This device came up with great fuzz in the USA for the enlargement of PNS ostia, especially the maxillary, frontal and sphenoidal sinuses for the treatment of nasosinusal inflammatory diseases 1,3,4,8 . This device dilates PNS ostia and its adjacent structures, causing local micro-fractures, through the use of a balloon capable of withstanding high pressures.…”
Section: Introductionmentioning
confidence: 99%
“…The trial showed a successful and persistent dilatation of sinus ostia in 80,5% of the patients. In 1,6% of the cases a persitent ostium could not be seen on endoscopy, in 17,9% of the cases the interior nose could not be assessed adequately by endoscopy (Bolger et al, 2007). Nine patients had developed bacterial sinusitis, which could be treated successfully by oral antibiotic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Patient´s eyes and the lenses are exposed to the radiation beam and it is not uncommon that patients, who are frequently exposed to radiation may develop cataract. The estimated radiation dose during Balloon Sinuplasty accounts to approximately 730 mrem (Bolger et al, 2007). In comparison the radiation dose of a CT scan of the head accounts to only 200 mrem, CT scan of the chest sums up to approximately 800 mrem.…”
Section: Discussionmentioning
confidence: 99%
“…In September 2005, Balloon Sinuplasty TM (Acclarent, Inc.) was introduced as a minimally invasive option to widen sinus ostia and their transition spaces while preserving the corresponding mucosa. The outcome, efficacy, and safety of the balloon dilation technology as applied to the frontal, maxillary and sphenoid sinuses has been well vetted and reported [2][3][4][5][6][7][8][9]. However, due to the complex drainage patterns and interconnected nature of the ethmoid complex, the balloon technology was not initially suited to treat chronic ethmoid disease [10].…”
Section: Introductionmentioning
confidence: 99%